The effect of DNA methylation on the miRNA expression pattern in lipopolysaccharide-induced inflammatory responses in human dental pulp cells. (July 2019) - Mo, Zehuan; Li, Qimeng; Cai, Luhui; Zhan, Minkang; Xu, Qiong
Highlights: DNA methylation was involved in the inflammation of human dental pulp cells (hDPCs). 5-Aza-CdR pretreatment changed the miRNA expression pattern in LPS-treated hDPCs. The expression of MIR146 A was regulated by DNA methylation in LPS-treated hDPCs. DNA methylation did not change the methylation pattern of MIR146A promoter in LPS-treated hDPCs. Abstract: Endodontic infection is a widespread oral problem. DNA methylation is a key epigenetic modification that plays important roles in various inflammatory responses, but its role in dental pulp inﬂammation is poorly understood. In this study, we assessed the expression of DNA methyltransferases (DNMTs) in human dental pulp cells (hDPCs) during lipopolysaccharide (LPS)-induced inflammation and found that DNMT3B mRNA expression was reduced and DNMT1 mRNA and protein levels decreased significantly. Pretreatment with the DNMT inhibitor 5-Aza-2'-deoxycytidine (5-Aza-CdR) significantly enhanced the expression of the inflammatory cytokines IL-6 and IL-8 in LPS-stimulated hDPCs, indicating that DNA methylation may play a role in hDPC inflammation. Studies have reported that some microRNAs (miRNAs) are involved in dental pulp infection. DNA methylation can modulate the inflammatory response by regulating miRNA expression, but this phenomenon has not yet been reported in pulp inﬂammation. The present study used next-generation sequencing to examine the effect of 5-Aza-CdR on the miRNA expression profile of LPS-treated hDPCs, and the results showed that 5-Aza-CdR pretreatment changed the miRNA expression pattern in hDPCs during inflammation. Among the changed miRNAs, miR-146a-5p, which is a pulp inflammation-related miRNA, demonstrated the most noticeably altered expression. miR-146a-5p could be induced by LPS in hDPCs, and 5-Aza-CdR preincubation or DNMT1 knockdown markedly increased its expression level. However, no significant difference was found in the methylation pattern of the MIR146A promoter with 5-Aza-CdR pretreatment or DNMT1 knockdown in LPS-stimulated hDPCs. These results indicate that DNA methylation may regulate the LPS-induced inflammatory response by changing the miRNA expression in hDPCs.